BEBERAPA PENDEKATAN UNTUK MEMAHAMI HUKUM - Purwaka, Tommy Hendra (Jurnal Hukum dan Peradilan, 2015)
Law in general is understood as regulations formed by authority to regulate community and its activities for the purpose of creating public order and justice. The law is enforced by legal apparatus by applying compliance and coercive measures. In addition, understanding on law can also be obtained by the use of several different approaches in viewing the law, such as fromÂ political, economic, social and cultural approaches. By so doing, understanding on law can be enriched and improved for the benefit of law enforcement and compliance.Keywords: Approaches, Understanding, Law